RETRACTED: Internet of Things security framework based on near field communication with Otway Rees protocol - Musa Jaber M.; Yussof S.; Ali M.H.; Khalil Abd S.; Jassim M.M.; Alkhayyat A. (John Wiley and Sons Inc, 2025)
Internet of Things (IoT) devices are crucial in different industries because they provide high-functioning services to the IoT network connectivity. The IoT devices collect sensitive data, which comes under potential risk while transmitting data from one location to another. The data transmission is performed using various communication protocols that give security to the data. The intermediate attacks such as jamming, collision, flooding, worm-hole, black-hole and so forth create several security-related issues. These intermediate attacks affect data privacy, trust, user identity, which completely affects the IoT device performance. So, this article introduces the near field communication (NFC) protocol with the Otway Rees protocol for making the secure communication process. In IoT applications based on short-range communication, intermediate attacker issues have been reduced by combining NFC protocol features with Otway Rees protocol features. The NFC protocol provides baseline security trustworthiness while making the communication in the IoT environment cost-effective. IoT communication is protected while cost-effective using the security model, ensuring data integrity and confidentiality. In addition to this, the user and servers are authenticated for every session, which provides data security. Moreover, the discussed system is implemented using the NS2 simulation tool, ensuring security and trust with minimum complexity. Even in abnormal traffic conditions, our proposed method resulted in data transmission speeds (up to 289 Kb/s), and this feature can improve processing times. ? 2022 John Wiley & Sons, Ltd.